Tasikmalaya Regency Regional Revenue and Expenditure Budget Policy Evaluation Model - Usman Kusmana; Thomas Bustomi; Kamal Alamsyah (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
This study examines the effectiveness of the Tasikmalaya Regency Regional Budget (APBD), which is not yet optimal due to administrative-oriented evaluation, low public participation, minimal transparency, and limited fiscal independence. The study aims to develop a comprehensive evaluation model that integrates budget performance, public participation, digital transparency, and fiscal independence. A mixed methods sequential explanatory approach was used with the Tasikmalaya community, regional apparatus, and legislative bodies; a sample of 200 survey respondents (purposive) and 15 interview informants (snowball). Instruments included questionnaires, interview guides, and secondary APBD data; quantitative descriptive and qualitative thematic analyses were integrated via joint display. The results showed 60% public satisfaction, 30% participation, 30% local revenue (PAD), and 40% budget knowledge. The conclusion states that the multidimensional model improves APBD accountability with recommendations for strengthening e-budgeting and Musrenbang.